Neuralized functions cell autonomously to regulate Drosophila sense organ development. - Yeh, E.; Zhou, L.; Rudzik, N.; Boulianne, G.L. (The EMBO Journal, 2000)
Neurogenic genes, including Notch and Delta, are thought to play important roles in regulating cell-cell interactions required for Drosophila sense organ development. To define the requirement of the neurogenic gene neuralized (neu) in this process, two independent neu alleles were used to generate mutant clones. We find that neu is required for determination of cell fates within the proneural cluster and that cells mutant for neu autonomously adopt neural fates when adjacent to wild-type cells. Furthermore, neu is required within the sense organ lineage to determine the fates of daughter cells and accessory cells. To gain insight into the mechanism by which neu functions, we used the GAL4/UAS system to express wild-type and epitope-tagged neu constructs. We show that Neu protein is localized primarily at the plasma membrane. We propose that the function of neu in sense organ development is to affect the ability of cells to receive Notch-Delta signals and thus modulate neurogenic activity that allows for the specification of non-neuronal cell fates in the sense organ.